ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI BANGUN RUANG DI KELAS VIII SMP NEGERI 5 SIPIROK - Nurholijah Pohan; Eva Yanti Siregar; Agus Saleh (JURNAL MathEdu (Mathematic Education Journal), 2021)
This study aimed to describe students’ mathematical problem solving ability on the topic cuboids figure at the eighth grade students of SMP Negeri Sipirok. The research was conducted by applying qualitative descriptive method with 5 students as the subject. Interview and test were used in collecting the data. The data was analysis by applying data reduction, data presentation, and taking conclusion. The result of the research showed (1) 2 students were high ability, (2) 2 students were average ability, and (3)1 students was low ability